Penggunaan Media Audio Visual untuk Meningkatkan Motivasi dan Hasil Belajar - Warno Dwi Antoro; Gunawan Sridiyatmiko (UM Purwokerto Press, 2022)
This research was aimed to know that using of audio visual media could increase motivation and learning outcome of social studies in elementary school. Method which used in this research was PTK it was consist of three cycles, each cycles has planning, implementation, observation and reflection. Result of this research showed that there was an increasing on: (1) student’s motivation to learn, which 56,25% on 1st cycle, 74,19% on 2nd , and 90% on 3rd cycle; (2) student’s learning outcomes in cognitive aspect increased from average value 69,53 on 1st cycle, 73,71 on 2nd cycle, 80,66 on 3rd cycle, in affective aspect was 56,25% on 1st cycle,74,19% on 2nd cycle, 90% on 3rd cycle, in psychomotor aspect increased from average value 70,08 on 1st cycle, 75,18 on 2nd cycle, and 80,59 on 3rd cycle. Implication, based on research was audio visual media could increase learning motivation and the increasing of learning motivation could increase learning outcome.